Gas, Water and Solid Waste Treatment Technology - Zhang, Zhien; Núñez-Delgado, Avelino; Zhang, Wenxiang (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book introduces a variety of treatment technologies, such as physical, chemical, and biological methods for the treatment of gas emissions, wastewater, and solid waste. It provides a useful source of information for engineers and specialists, as well as for undergraduate and postgraduate students, in the areas of environmental science and engineering.